The role of allogeneic hematopoietic cell transplantation for chronic lymphocytic leukemia: A review - Puckrin, Robert; Shafey, Mona; Storek, Jan (Frontiers in Oncology, 2023)
Although the use of allogeneic hematopoietic cell transplantation (HCT) for chronic lymphocytic leukemia (CLL) has declined with the development of novel targeted agents, it continues to play an important role for eligible patients with high-risk or heavily pretreated CLL who lack other treatment options. CLL is susceptible to a potent graft-versus-leukemia (GVL) effect which produces long-lasting remissions in 30-50% of transplanted patients. While allogeneic HCT is associated with significant risks of graft-versus-host disease (GVHD), infection, and non-relapse mortality (NRM), improvements in patient and donor selection, reduced intensity conditioning (RIC), GVHD prophylaxis, and supportive care have rendered this an increasingly safe and effective procedure in the current era. In this review, we discuss recent advances in allogeneic HCT for CLL, with a focus on the optimal evidence-based strategies to maximize benefit and minimize toxicity of this potentially curative cellular therapy.